Involvement of interferon γ-producing mast cells in immune responses against melanocytes in vitiligo requires Mas-related G protein-coupled receptor X2 activation - Zhikai Liao; Yunzhu Yao; Bingqi Dong; Yue Le; Longfei Luo; Fang Miao; Shan Jiang; Tiechi Lei; Lishao Guo (Chinese Medical Journal)
Abstract. Background:. Increasing evidence indicates that oxidative stress and interferon γ (IFNγ)-driven cellular immune responses are responsible for the pathogenesis of vitiligo. However, the connection between oxidative stress and the local production of IFNγ in early vitiligo remains unexplored. The aim of this study was to identify the mechanism underlying the production of IFNγ by mast cells and its impact on vitiligo pathogenesis. Methods:. Skin specimens from the central, marginal, and perilesional skin areas of active vitiligo lesions were collected to characterize changes of mast cells, CD8+ T cells, and IFNγ-producing cells. Cell supernatants from hydrogen peroxide (H2O2)-treated keratinocytes (KCs) were harvested to measure levels of soluble stem cell factor (sSCF) and matrix metalloproteinase (MMP)-9. A murine vitiligo model was established using Mas-related G protein-coupled receptor-B2 (MrgB2, mouse ortholog of human MrgX2) conditional knockout (MrgB2−/−) mice to investigate IFNγ production and inflammatory cell infiltrations in tail skin following the challenge with tyrosinase-related protein (Tyrp)-2 180 peptide. Potential interactions between the Tyrp-2 180 peptide and MrgX2 were predicted using molecular docking. The siRNAs targeting MrgX2 and the calcineurin inhibitor FK506 were also used to examine the signaling pathways involved in mast cell activation. Results:. IFNγ-producing mast cells were closely aligned with the recruitment of CD8+ T cells in the early phase of vitiligo skin. sSCF released by KCs through stress-enhanced MMP9-dependent proteolytic cleavage recruited mast cells into sites of inflamed skin (Perilesion vs. lesion, 13.00 ± 4.00/high-power fields [HPF] vs. 26.60 ± 5.72/HPF, P <0.05). Moreover, IFNγ-producing mast cells were also observed in mouse tail skin following challenge with Tyrp-2 180 (0 h vs. 48 h post-recall, 0/HPF vs. 3.80 ± 1.92/HPF, P <0.05). The IFNγ+ mast cell and CD8+ T cell counts were lower in the skin of MrgB2−/−mice than in those of wild-type mice (WT vs. KO 48 h post-recall, 4.20 ± 0.84/HPF vs. 0.80 ± 0.84/HPF, P <0.05). Conclusion:. Mast cells activated by MrgX2 serve as a local IFNγ producer that bridges between innate and adaptive immune responses against MCs in early vitiligo. Targeting MrgX2-mediated mast cell activation may represent a new strategy for treating vitiligo.